The rave catalog of stellar elemental abundances: first data release - Boeche, Corrado; Siebert, A.; Williams, M.; Jong, R. S. de; Steinmetz, M.; Fulbright, J. P.; Ruchti, G. R.; Bienaymé, O.; Bland-Hawthorn, J.; Campbell, R.; Freeman, K. C.; Gibson, B. K.; et al. (The astronomical journal, 2011)
We present chemical elemental abundances for 36,561 stars observed by the RAdial Velocity Experiment (RAVE), an ambitious spectroscopic survey of our Galaxy at Galactic latitudes |b| > 25° and with magnitudes in the range 9 <IDENIS <13. RAVE spectra cover the Ca-triplet region at 8410-8795 Å with resolving power R ∼ 7500. This first data release of the RAVE chemical catalog is complementary to the third RAVE data release of radial velocities and stellar parameters, and it contains chemical abundances for the elements Mg, Al, Si, Ca, Ti, Fe, and Ni, with a mean error of ∼0.2 dex, as judged from accuracy tests performed on synthetic and real spectra. Abundances are estimated through a dedicated processing pipeline in which the curve of growth of individual lines is obtained from a library of absorption line equivalent widths to construct a model spectrum that is then matched to the observed spectrum via a χ2 minimization technique. We plan to extend this pipeline to include estimates for other elements, such as oxygen and sulfur, in future data releases.
Gesehen am 31.03.2022